HTRA2 Defect: A Recognizable Inborn Error of Metabolism with 3-Methylglutaconic Aciduria as Discriminating Feature Characterized by Neonatal Movement Disorder and Epilepsy—Report of 11 Patients - Kovacs-Nagy, Reka; Morin, Gilles; Nouri, Maria Al; Brandau, Oliver; Saadi, Nebal Waill; Nouri, Mohammed A.; van den Broek, Florence; Prokisch, Holger; Mayr, Johannes A.; Wortmann, Saskia B. (Neuropediatrics, 2018)
Neonatal-onset movement disorders, especially in combination with seizures, are rare and often related to mitochondrial disorders. 3-methylglutaconic aciduria (3-MGA-uria) is a marker for mitochondrial dysfunction. In particular, consistently elevated urinary excretion of 3-methylglutaconic acid is the hallmark of a small but growing group of inborn errors of metabolism (IEM) due to defective phospholipid remodeling or mitochondrial membrane-associated disorders (mutations in TAZ, SERAC1, OPA3, CLPB, DNAJC19, TMEM70, TIMM50). Exome/genome sequencing is a powerful tool for the diagnosis of the clinically and genetically heterogeneous mitochondrial disorders. Here, we report 11 individuals, of whom 2 are previously unpublished, with biallelic variants in high temperature requirement protein A2 (HTRA2) encoding a mitochondria-localized serine protease. All individuals presented a recognizable phenotype with neonatal- or infantile-onset neurodegeneration and death within the first month of life. Hallmark features were central hypopnea/apnea leading to respiratory insufficiency, seizures, neutropenia, 3-MGA-uria, tonus dysregulation, and dysphagia. Tremor, jitteriness, dystonia, and/or clonus were also common. HTRA2 defect should be grouped under the IEM with 3-MGA-uria as discriminating feature. Clinical characteristics overlap with other disorders of this group suggesting a common underlying pathomechanism. Urinary organic acid analysis is a noninvasive and inexpensive test that can guide further genetic testing in children with suggestive clinical findings.
Keywords: mitochondrial dysfunction; developmental delay; respiratory insufficiency; dystonia; tremor